1993
DOI: 10.1017/s0022112093001193
|View full text |Cite
|
Sign up to set email alerts
|

Resonance in axisymmetric jets with controlled helical-mode input

Abstract: This work involves active control of fundamental two- and three-dimensional amplified modes in an axisymmetric jet by introducing localized acoustic disturbances produced by an azimuthal array of miniature speakers placed close to the jet lip on the exit face. The independent control of each speaker output allowed different azimuthal amplitude and phase distributions of periodic inputs. The types of inputs used in this study consisted of conditions to force helical mode pairs with the same frequency and equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…At low speeds, it was possible in laboratory to introduce helical modes with specified frequencies and azimuthal wavenumbers, and follow their nonlinear interaction (Cohen & Wygnanski 1987b, Long & Petersen 1992, Corke & Kusek 1993. A verification of the mechanism proposed in the present paper would require extending these controlled excitation techniques to the compressible regime to generate m = ±1 modes, and to carry out simultaneous acoustic measurements.…”
Section: Discussionmentioning
confidence: 69%
“…At low speeds, it was possible in laboratory to introduce helical modes with specified frequencies and azimuthal wavenumbers, and follow their nonlinear interaction (Cohen & Wygnanski 1987b, Long & Petersen 1992, Corke & Kusek 1993. A verification of the mechanism proposed in the present paper would require extending these controlled excitation techniques to the compressible regime to generate m = ±1 modes, and to carry out simultaneous acoustic measurements.…”
Section: Discussionmentioning
confidence: 69%
“…The momentum thickness of the natural jet is θ m = 0.17 mm, thus giving θ m /D = 0.0085. Previous investigations [35][36][37] have confirmed that the initial region of an axisymmetric jet surrounded by a thin initial shear layer (θ m /D 1) is equally unstable to an axisymmetric (m = 0) as well as to the first helical modes (m = + or −1). Samimy et al [7] achieved a higher enhancement of jet mixing and a faster decay rate of jet centreline velocity by exciting a round jet with the m = ±1 mode at the jet preferredmode frequency than that excited with the m = 0 mode at the same frequency, where the m = 0, ±1 modes are forced by changing the way actuators are operated.…”
Section: Performance and Role Of The Minijet Actuatormentioning
confidence: 87%
“…Corke & Kusek (11) introduced localized acoustic disturbances, which were produced by an array of miniature loud speakers placed around the jet nozzle exit. Smith & Glezer (12) successfully applied miniature zero-massflux jet actuators (synthetic jets) for the control of a largescale planar jet.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the previous studies mentioned above, the control input mode introduced is limited to one or a few. Corke and Kusek (11) studied the effect of the jet nozzle equipped with 12 miniature speakers mounted at the exit. Their control modes were only the helical modes of n = 0 and ±1, where n denotes the azimuthal wave number.…”
Section: Introductionmentioning
confidence: 99%